Utilización de las Hojas de Piña para Elaborar Telares - Huallpa Oscanoa, Evelyn (2019)
The objective of this research work is to use pineapple leaves in stubble to make tissues; thus avoiding the inadequate management of final disposal of agricultural residues of pineapple production. The leaves of the pineapple plants that remain in the agricultural fields after the harvest of the fruit, we can give them other uses, since many times they are incinerated, generating polluting gases. The methodology consisted in leaving only the fibers of the leaf removing the non-fibrous substances by empirical methods in manual form, the drying was carried out and later the knitting was done with sticks of pineapple leaves of three varieties: Golden, Hawaiana and variety. As a procedure, the pineapple leaves fibers were extracted manually and the knitting was done with hand-made instruments. As results, it was obtained that the tissue of the pineapple leaf residue of the Hawaiana variety presents better quality with an average tensile strength of 6.041 MPa and elongation of 312.4%, this means that the sample has been stretched 3 times its initial length, this shows that the Hawaiian variety is more resistant than the Golden variety with tractive force of 5,560 MPa and average elongation 222.9% the average variety samba of tensile force 4,051 MPa and Elongation average 270,9%. According to its resistance of the tissues it can be classified that the fabric of the Hawaiian variety according to the characteristics found can be of use of bags and purses.